An evaluation of water quality of Sepang Kecil river in Selangor / Nurain Fatihah Abdul Raof - Nurain Fatihah , Abdul Raof (2017)
This study was conducted once a month from May 2014 to February 2015 at five sampling stations. This study was carried out to determine the water quality of the Sepang Kecil River based on the Water Quality Index (WQI) and the diversity of phytoplankton. A total of 19 parameters were analyzed which were the water temperature, pH, total dissolved solid (TDS), conductivity, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), suspended solid (SS), turbidity, salinity, ammoniacal nitrogen (NH3-N), chlorophyll a and including seven anions of fluoride, chloride, nitrite, bromide, nitrate, phosphate, and sulphate. Based on the National Water Quality Standard of Malaysia (NWQS), the result showed that DO, BOD, NH3-N and SS fall under Class III while pH, conductivity and TDS were categorized under Class I. Other than that, the turbidity and the COD were classified under Class II and Class IV respectively. Based on the NWQS for Malaysia, only fluoride and chloride were classified under Class I and Class II respectively while the rest of the anions fall under Class V. Based on the ANOVA analysis from the SPSS (Statistical Package for the Social Sciences) programme, it was found that the DO, BOD, NH3-N and the salinity shown a significant difference in between the five stations and the nine months. Overall, the WQI for the Sepang Kecil River was recorded as slightly polluted which was classified into Class III with the value of 69.0. A total of 37 species from four divisions namely Bacillariophyta, Chlorophyta, Cyanobacteria, and Pyrrophyta were recorded during this study. Division of Chlorophyta and Bacillariophyta were dominated in this study. The results from the water quality classification based on overall H’ values showed slightly polluted level and high diversity of phytoplankton was found in the downstream of the Sepang Kecil River. Phytoplankton has a positive correlation with BOD, COD, NH3-N, conductivity, salinity and chlorophyll a, nitrite, bromide, phosphate and sulphate.